Black soldier fly technology transforming agri-food systems - Adamtey, Noah; Cofie, Olufunke O.; Atampugre, Gerald (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Rising from mountains of food waste to soil and water contamination, and a changing climate, the perils loom large. Global food security and sustainability are hanging by a delicate thread that commands attention. For sustainable Agri-Food Systems, the black soldier fly larvae (BSF) technology has emerged as a transformative force and a potential game-changer in waste management, soil health enhancement, animal feed production, water savings, carbon mitigation, agricultural and environmental sustainability. BSF technology is the circular economy’s’ new hero, turning waste into protein, fertilizer, oil, plastics, and more! But safety, regulations, smarter and cost-effective production are key. Let’s invest in innovative R & D, scale up production, highlight the quality and nutritional food, and jobs that the technology can create, prioritize strategic planning to bolster market penetration, credibility, and competitiveness.